Follicular CD4 T Helper Cells As a Major HIV Reservoir Compartment: A Molecular Perspective - Aid, Malika; Dupuy, Frank P.; Moysi, Eirini; Moir, Susan; Haddad, Elias K.; Estes, Jacob D.; Sekaly, Rafick Pierre; Petrovas, Constantinos; Ribeiro, Susan Pereira (Frontiers in Immunology, 2018)
Effective antiretroviral therapy (ART) has prevented the progression to AIDS and reduced HIV-related morbidities and mortality for the majority of infected individuals. However, a lifelong administration of ART is necessary, placing an inordinate burden on individuals and public health systems. Therefore, discovering therapeutic regimens able to eradicate or functionally cure HIV infection is of great importance. ART interruption leads to viral rebound highlighting the establishment and maintenance of a latent viral reservoir compartment even under long-term treatment. Follicular helper CD4 T cells (TFH) have been reported as a major cell compartment contributing to viral persistence, consequent to their susceptibility to infection and ability to release replication competent new virions. Here, we discuss the molecular profiles and potential mechanisms that support the role of TFH cells as one of the major HIV reservoirs.